In Honor of Professor Serge Galam for His 70th Birthday and Forty Years of Sociophysics (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Sociophysics emerged in the 1980s as a groundbreaking research field, paralleling physicists’ growing interest in understanding complex systems across diverse domains. By adapting methods from statistical physics—originally developed to explain critical phenomena, random systems, and non-equilibrium dynamics—researchers began applying these tools outside the natural sciences. However, tackling economic and social science problems with a physics-based approach, without the foundational laws of conservation or symmetry, posed a formidable challenge. Nevertheless, thanks to the dedication of several pioneering scientists and despite an unavoidable skepticism for novelty, sociophysics is now established as a recognized domain, with a thriving community of researchers and many success stories. Science is about pushing the frontiers of knowledge, and sociophysics exemplifies such an endeavor. Using methods from physics, mathematics, and, increasingly, from computational science, researchers can now ask previously unexplored questions, using rigorous and quantitative tools, so as to develop a new, creative synergy with social scientists. This Special Issue highlights the achievements of sociophysics through cutting-edge contributions from renowned experts. It is dedicated to Serge Galam, a pioneering figure in the field, in celebration of his 70th birthday.